2015
DOI: 10.1007/s11426-015-5445-3
|View full text |Cite
|
Sign up to set email alerts
|

Celestine blue as a new indicator in electrochemical DNA biosensors

Abstract: Celestine blue (CB) was introduced as a new electroactive indicator in DNA biosensors. The interaction of CB with DNA was investigated by electrochemical and spectroscopic methods. The effect of buffer kind and pH on the electrochemical behavior of CB was studied. The peak currents of CB were linearly related to DNA concentration in the range of 5.0×10 −9 to 1.0×10 −7 mol/L. The detection limit of this approach was 4.76×10 −10 mol/L. Based on spectrometry data a hypochromic effect was observed in UV-Vis spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…CB molecules bind to DNA molecules through electrostatic interactions. . After incubation of the modified electrode with CB, a pair of well defined reversible peaks was observed due to the electrochemical oxidation/reduction of the adsorbed CB (the inset of Figure .A).…”
Section: Resultssupporting
confidence: 83%
“…CB molecules bind to DNA molecules through electrostatic interactions. . After incubation of the modified electrode with CB, a pair of well defined reversible peaks was observed due to the electrochemical oxidation/reduction of the adsorbed CB (the inset of Figure .A).…”
Section: Resultssupporting
confidence: 83%
“…The results exhibited that current signal of S2 was not affected by the mismatched sequences, indicating the sensor could perfectly distinguish the target from various interference sequences ( Figure 5 C). Compared with the Bazgir’s work [ 19 ], our further study in the sequence selectivity and anti-interference experiments showed its great potential in clinical diagnosis.…”
Section: Resultsmentioning
confidence: 75%
“…So it can be used as a promising hybridization indicator via binding to nucleic acids by electrostatic attraction, which can be employed in electrochemical DNA biosensors. Bazgir et al [ 19 ] designed the CB-modified carbon paste electrode and investigated the interaction mode between CB and nucleic acid through spectroscopic and electrochemical approaches. The detection limit of this approach was as low as 0.48 nM.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine abuse results a state of "dreamy intoxication", blurred vision and out of body experiences [7][8][9][10][11][12]. Recently, interaction of DNA and drugs has been a growing attractive topic in the electrochemical investigations [13][14][15][16]. For small molecules such as drugs, mechanism of interaction as well as evaluation of binding constant can be investigated by electrochemical studies.…”
Section: Introductionmentioning
confidence: 99%